Bacteria Community Inhabiting Heterobasidion Fruiting Body and Associated Wood of Different Decay Classes - Ren, Wenzi; Penttilä, Reijo; Kasanen, Risto; Asiegbu, Fred O. (Frontiers in Microbiology, 2022)
The microbiome of Heterobasidion induced wood decay of living trees has been previously studied, however little is known about the bacteria biota of its perennial fruiting body and the adhering wood tissue. In this study, we investigated the bacteria biota of the Heterobasidion fruiting body and its adhering deadwood. There was a total of 7,462 OTUs, about 5,918 OTUs were from the fruiting body and 5,469 OTUs from the associated dead wood. Interestingly, an average of 52.6% of bacteria biota in fruiting body were shared with the associated dead wood. The overall and unique OTUs had trends of decreasing from decay classes one to three but increasing in decay class four. Fruiting body had the highest overall and unique OTUs number in the fourth decay class, while wood had the highest OTU in decay class one. Sphingomonas spp. was significantly higher in the fruiting body and phylum Firmicutes was more dominant in wood tissue. FAPROTAX functional structure analysis revealed nutrition, energy, degradation, and plant-pathogen related functions of the communities. Our results also showed that bacteria communities in both substrates experienced a process of a new community re-construction through the various decay stages. The process was not synchronic in the two substrates, but the community structures and functions were well-differentiated in the final decay class. The bacteria community was highly dynamic, the microbiota activeness, community stability, and functions changed with the decay process. The third decay class was an important turning point for community re-structuring. Host properties, environmental factors, and microbial interactions jointly influenced the final community structure. Bacteria community in fruiting body attached to the living standing tree was suppressed compared to those associated with dead wood. Bacteria appear to spread from wood tissue of standing living tree to fruiting body, but after the tree is killed, bacteria moved from fruiting body to wood. It is most likely some of the resident endophytic bacteria within the fruiting body are either parasitic, dependent on it for their nutrition, or are mutualistic symbionts.